Separating Birth from Community: Colonialism and Historical Institutionalism in Indigenous Pregnancy Evacuation Policies - Sabrina Lee; Angela Mashford-Pringle (McMaster University Library Press, 2024)
Evacuating pregnant Indigenous individuals who live in remote communities to urban centres for birthing is not a formal or written policy in Canada, but has been the norm for several decades. Canada is a geographically large country with remote communities, often inhabited by Indigenous peoples, which provides universal health care to communities spanning from the Pacific to Atlantic oceans. The evacuation of pregnant Indigenous peoples has resulted in a disconnection between birth and community, land, ceremony, and Traditional Healing. This policy displacing pregnant Indigenous women has been reportedto bring them emotional, financial, and physical harm. Historical institutionalism may be precluding significant change to the norm of maternal evacuation. Euro-Canadian epistemologies and colonial mindsets have prevented biomedical institutions from seeing the detachment from land and community as a problem, as the transfer to tertiary hospitals may have been considered beneficial for Indigenous women. Indigenous self-determination in reforming Indigenous maternity care policies is crucial in addressing this health systems issue. L'évacuation des personnes enceintes autochtones vivant en communautés isolées vers des centres urbains pour y accoucher n'est pas une politique officielle, ni écrite, au Canada, mais la norme existe depuis plusieurs dizaines d'années. Le Canada est un pays géographiquement vaste comptant de nombreuses communautés isolées, souvent habitées par des personnes autochtones, et fournissant des soins de santé universels aux communautés qui s'étendent de l'océan Pacifique à l'océan Atlantique. L'évacuation des personnes enceintes autochtones a entraîné une déconnexion entre la naissance et la communauté, la terre, les cérémonies et la guérison traditionnelle. Cette politique de déplacement des femmes enceintes autochtones leur causent des effets néfastes émotionnels, financiers et physiques. L'institutionnalisme historique peut empêcher un changement significatif de la norme d'évacuation des mères. Les épistémologies euro-canadiennes et les mentalités coloniales ont empêché les institutions biomédicales de considérer le détachement de la terre et de la communauté comme un problème, car le transfert vers des hôpitaux tertiaires a pu être considéré comme bénéfique pour les femmes autochtones. L'autodétermination autochtone par rapport à la réforme des politiques de soins obstétricaux chez les personnes autochtones est cruciale pour résoudre ce problème de systèmes de santé.